Radiofrequency versus cryoballoon ablation for atrial fibrillation: an argument for a 'cryo-first' approach. (January 2020) - Tomaiko, Emrie; Tseng, Andrew; Su, Wilber W.
Abstract : Purpose of review: Radiofrequency and cryoballoon ablation are the two most common modalities for catheter ablation of atrial fibrillation. Radiofrequency, being more prevalent and having existed for a longer period, is often utilized for patients' first ablations, despite the efficiency and efficacy of the cryoballoon tool. Here we examine the advantages of the cryoballoon for its use in first-time ablation of atrial fibrillation. Recent findings: The FIRE & ICE trial is established as conclusive evidence of the noninferiority of cryoballoon ablation to radiofrequency ablation in terms of efficacy. Since the study, cryoballoon has evolved in both form and technique, suggesting need for repeat consideration of the advantages of cryoablation over radiofrequency ablation. The second-generation cryoballoon has led to greater efficiency in achieving permanent pulmonary vein isolation, reducing complications, and reducing procedure times. Summary: There are advantages to the use of cryoballoon which could increase success of first-time ablations, delaying need for repeat procedure and lowering overall burden on patients and the healthcare system. Cryoballoon ablation should be considered for first-time ablation in patients with paroxysmal or persistent atrial fibrillation.